Model of Teaching English Speaking Practiced for English Department Students at IAIN Palopo - Roni La'biran (STAI Hubbulwathan Duri, 2022)
The objectives of the research are to discover models of teaching speaking practiced at IAKN Palopo, students’ perceptions of teaching models, teaching speaking models to students’ speaking achievement.The researcher employed qualitative methods for the study. The data resources for the research chosen through random sampling lectures at IAIN Palopo. The instruments for the research consist of observations, interviews in analyzing the data, the researcher employed a qualitative method.The results show that the models of teaching speaking practiced at IAKN Palopo is presentation, practice, production model (PPP) the model divided into three phases as follow: Presentation, refers to new topic and contextualizing, teaching Demonstration (cookies activities), teaching English based on classroom situation. Practice refers to learners practice the structure using accurate reproduction techniques including choral and individual repetition and cue-response drills, students did demonstration based on lecturer’s instruction and Students’ perception toward the model is good, there is positive indicator perception because almost students said, happy, lecturer as a good figure in teaching speaking, simple material.